Guidelines for listening and helping - Larson, Dale G. (San Carlos, CA : Scro Pub., 1991)
This program teaches helping and self-care skills to volunteer and professional caregivers working with people who face life-threatening illness, dying, and bereavement
Producer/director, ROnald Scro ; executive producer, Sr. Patricia Marie Mulpeters ; author, Dale G. Larson
Keywords: Helping behavior; Grief -- therapy; Counseling